2019
DOI: 10.1159/000501515
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment with Antibiotics and Glucocorticosteroids for Severe Ischemic Colitis

Abstract: Background/Aims: Ischemic colitis (IC) is most common in the elderly and patients with multiple comorbidities. It carries significant mortality. As yet no evidence-based therapeutic management exists. Aim of the study was to test therapeutic efficacy of a combination of prednisolone and antibiotics. Methods: Prospective cohort study with retrospective analysis performed in a single teaching hospital in Germany. Consecutive patients with strict diagnostic criteria of severe IC, including colonoscopy, histology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, Wolfgang Kruis et al recently suggested a potential protective effect of the combination of intravenous antibiotics and intravenous prednisolone for cases of severe IC. This preliminary study may offer a new pathway for the field of study of conservative management of severe IC [67]; however, this result still needs further exploration.…”
Section: Glucocorticosteroidsmentioning
confidence: 91%
“…However, Wolfgang Kruis et al recently suggested a potential protective effect of the combination of intravenous antibiotics and intravenous prednisolone for cases of severe IC. This preliminary study may offer a new pathway for the field of study of conservative management of severe IC [67]; however, this result still needs further exploration.…”
Section: Glucocorticosteroidsmentioning
confidence: 91%
“…However, recovery may be protracted with bowel rest alone, and surgical intervention may be necessary in some severe cases. Kruis and Schiff[ 10 ] reported that combination therapy with intravenous antibiotics and prednisolone showed promising therapeutic effects without safety concerns in cases of moderate-to-severe ischemic colitis. Antimicrobial therapy can effectively reduce pathogenic bacteria, bacterial translocation, and inflammatory responses to ischemic injury[ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HPA axis is a complex regulatory system with direct and feedback interaction composed of the hypothalamus, pituitary gland, and adrenal gland. The HPA axis is an integral part of the neuro-endocrine system, involved in controlling responses to stress or infection and serving to restore the homeostasis, and regulating a variety of physical activities, immune system, emotion, and digestion [ 19 , 20 ]. When the body is exposed to stressors, various cytokines (such as TNF-α, IL-1β, and IL-6) secreted by immune cells act as critical molecular signals that trigger the activation of HPA axis [ 3 ].…”
Section: Discussionmentioning
confidence: 99%